Optimizing dissection, sample collection and cell isolation protocols for frugivorous bats. Issue 1 (2nd December 2019) - Irving, Aaron T.; Ng, Justin H. J.; Boyd, Victoria; Dutertre, Charles‐Antoine; Ginhoux, Florent; Dekkers, Milou H.; Meers, Joanne; Field, Hume E.; Crameri, Gary; Wang, Lin‐Fa
Abstract: Bats are becoming increasingly important as an experimental model due to their unique biological features. These include the ability of powered flight, minimal consequences from a heightened metabolic state, extended longevity in most species and minimal inflammation in response to most otherwise pathogenic viruses. To date there has been limited work done on the optimal procedures for necropsy, extraction of tissues or preparation of cell suspensions for downstream experimental work. Here we use Pteropus alecto black flying fox as an example model of the fruit bat to develop optimal procedures for anaesthetizing, necropsy methods, safety, sequence and protocols for cell/tissue extraction and isolation protocols. These methods were successfully used to yield high‐quality RNA, DNA and protein samples from tissues along with viable cells for various molecular and immunological studies. Procedures utilized are suitable for comparative biology studies with most protocols being directly modified from those used in mice and humans. While mainly optimized for the larger fruit bats (flying foxes) in this study, the majority of protocols can readily be adapted to all species of bats. This study provides the framework for greater consistency with in vivo bat experiments, application for comparative biology studies and greater engagement of the bat community for suitable protocols to be harmoniously adopted.